2022
DOI: 10.1021/acs.chemrestox.2c00087
|View full text |Cite
|
Sign up to set email alerts
|

Human TREX1 Repairs 3′-End DNA Lesions in Vitro

Abstract: Human three-prime repair exonuclease 1 (TREX1) is the major 3′ to 5′ exonuclease that functions to deplete the cytosolic DNA to prevent the autoimmune response. TREX1 is upregulated and translocates from cytoplasm to the nucleus in response to genotoxic stress, but the function of nuclear TREX1 is not well understood. Herein, we wish to report our in vitro finding that TREX1 efficiently excises 3′-phospho-α,β-unsaturated aldehyde and 3′-deoxyribose phosphate that are commonly produced as base excision repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…3′-PUA was prepared as a control by heating the AP site as previously described. 17 We found that nearly all nonreduced DPCs (Figure 2B proposed 3′-PUA-PARP1 DPC structure (Figure 1). This also indicates that the initially formed Schiff base 3′-PUA-PARP1 DPC intermediate is hydrolyzed before or after the Michael addition.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…3′-PUA was prepared as a control by heating the AP site as previously described. 17 We found that nearly all nonreduced DPCs (Figure 2B proposed 3′-PUA-PARP1 DPC structure (Figure 1). This also indicates that the initially formed Schiff base 3′-PUA-PARP1 DPC intermediate is hydrolyzed before or after the Michael addition.…”
mentioning
confidence: 77%
“…Specifically, the isolated PARP1-DPC without or with prior reduction by NaBH 4 was reacted with ARP, followed by proteinase K treatment and urea-PAGE analysis. 3′-PUA was prepared as a control by heating the AP site as previously described . We found that nearly all nonreduced DPCs (Figure B, Lanes 5–6), but not the reduced DPCs (Figure B, Lanes 1–2), were converted to slower migrating products (i.e., proteolyzed 3′-PUA-PARP1-ARP).…”
mentioning
confidence: 99%
“…We did a control experiment and demonstrated that this has little effect on the repair. Specifically, an oligonucleotide (Table S1, O4) containing 6-carboxyfluorescein (6-FAM) at the 5′-terminus and 3′-PUA was prepared as previously described 18 and then reacted with O-2propynylhydroxylamine 19 (AA3, Figure 2A). The resulting 3′-PUA-alkyne was purified by urea-PAGE, and the correct molecular weight was confirmed by MALDI-TOF mass spectrometry (Figure S1).…”
Section: Pua Through Oxime Ligation;mentioning
confidence: 99%